2016
DOI: 10.1177/1687814016645492
|View full text |Cite
|
Sign up to set email alerts
|

A study on properties of a cone-type brake for motor vehicle winch

Abstract: The brake of winch is to prevent the occurrence of reverse slipping at working time. Based on the analysis of two types of brake, this article establishes the relationship model of the brake force and the angle of the screw thread on the brake shaft and builds the model of the relationship of the brake force and the height of the cone and found that the brake force is the largest when the angle of the screw is 45°. Also found that the brake force increases with the increase in the load, and the brake force is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…The study in [10] introduces the structural composition and working principle of the cone brake, analyzes the advantages of the cone brake, through comparison with the drum brake, gives optimization suggestions for the shortcomings existing, and explores application prospects of new brakes. Research in [11] has shown that the cone brake can reduce the occurrence of harmful friction improve the efficiency of the winch, and can solve the winch safety problem caused by temperature build-up. The study in [11] also established a model of the brake force Engineering relationship and the angle of inclination of the screw thread on the brake shaft.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study in [10] introduces the structural composition and working principle of the cone brake, analyzes the advantages of the cone brake, through comparison with the drum brake, gives optimization suggestions for the shortcomings existing, and explores application prospects of new brakes. Research in [11] has shown that the cone brake can reduce the occurrence of harmful friction improve the efficiency of the winch, and can solve the winch safety problem caused by temperature build-up. The study in [11] also established a model of the brake force Engineering relationship and the angle of inclination of the screw thread on the brake shaft.…”
Section: Introductionmentioning
confidence: 99%
“…Research in [11] has shown that the cone brake can reduce the occurrence of harmful friction improve the efficiency of the winch, and can solve the winch safety problem caused by temperature build-up. The study in [11] also established a model of the brake force Engineering relationship and the angle of inclination of the screw thread on the brake shaft. Research in [11] also builds a model, finds the relationship between braking force and cone height, and finds the largest braking force.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation